Challenges and Solutions: A Case Study of Coca-Cola Company - Ju Yun Chua; Daisy Mui Hung Kee; Hadeel Ahmad Alhamlan; Pei Ying Lim; Qi You Lim; Xin Yin Lim; Niharika Singh (AIBPM Publisher, 2020)
Innovation and transformation are the key points to business success. Coca- Cola is the world’s largest distributor and producer of soft drink concentrates and syrups. Starting as a beverage manufacturer and retailer in 1886 with its flagship product, Coca-Cola. The marketing strategies, innovation and transformation are embedded in different culture that led to the sustainable growth of Coca-Cola Company. Across the globe and around the clock, Coca-Cola Company never stops working to improve the world we all shared and to give people the beverage they want. Some actions need to be taken on sugar reduction as consumers are adopting healthier lifestyle and innovations in packing materials by reducing the use of plastics.